2007
DOI: 10.1095/biolreprod.107.061788
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Function for CRISP1 in Rodent Fertilization: Involvement in Sperm-Zona Pellucida Interaction1

Abstract: Epididymal protein CRISP1 participates in rat and mouse gamete fusion through its interaction with complementary sites on the egg surface. Based on in vivo observations, in the present study we investigated the possibility that CRISP1 plays an additional role in the sperm-zona pellucida (ZP) interaction that precedes gamete fusion. In vitro fertilization experiments using zona-intact rat and mouse eggs indicated that the presence of either an antibody against rat CRISP1 (anti-CRISP1) or rat native CRISP1 (rCRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
0
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 43 publications
5
54
0
3
Order By: Relevance
“…These results are consistent with our recent report proposing a novel role for CRISP1 in sperm-ZP interaction (Busso et al, 2007a). In addition, and in agreement with the postulated role of CRISP1 in gamete fusion, in vitro assays using ZP-free eggs showed a significant reduction in the fusion ability of Crisp1 -/-sperm ( Figure 2D).…”
supporting
confidence: 93%
See 1 more Smart Citation
“…These results are consistent with our recent report proposing a novel role for CRISP1 in sperm-ZP interaction (Busso et al, 2007a). In addition, and in agreement with the postulated role of CRISP1 in gamete fusion, in vitro assays using ZP-free eggs showed a significant reduction in the fusion ability of Crisp1 -/-sperm ( Figure 2D).…”
supporting
confidence: 93%
“…Indirect immunofluorescence experiments revealed that rCRISP1 is capable of binding to both the ZP and the egg plasma membrane, suggesting the existence of CRISP1-binding sites on the ZP. Subsequent experiments using recCRISP1 as well as deglycosylated and heat-denatured native CRISP1 showed that this ZP-binding activity resides in the peptidic region of the molecule and depends on its conformation (Busso et al, 2007a). Recent results indicate that hCRISP1, like its rodent homologues, is involved in sperm-ZP interaction (Maldera et al, 2009).…”
Section: Crisp1mentioning
confidence: 99%
“…However, prior to the acrosome reaction, CRISP1 immunoreactivity is localized on the dorsal aspect of the sperm head, a location suggestive of a role in binding to the ZP. The ability of anti-CRISP1 antibodies and native CRISP protein to competitively inhibit sperm binding to the ZP is consistent with this possibility, although the nature by which CRISP is thought to facilitate binding remains unclear (Busso et al, 2007).…”
Section: Protein Based Recognition During Sperm-zp Bindingmentioning
confidence: 67%
“…Although not tested, it is anticipated that this activity will be via the suppression of Ca 2ϩ entry into sperm via ion channels (Roberts et al, 2003). The E form, on the other hand, binds tightly to the sperm in uncapacitated sperm and appears to re-distribute to the equatorial region of the sperm head (Rochwerger and Cuasnicu, 1992) where it is hypothesized to have a role in spermoocyte binding (Cohen et al, 2000;Busso et al, 2007). The mechanism of this potential activity is currently unknown, but the addition of peptides corresponding to the CAP domain signature motifs and cell transfection experiments using truncated forms of CRISP2 suggest that there is a CAP protein involved in sperm-oocyte binding via the CAP domain (Maeda et al, 1999;Ellerman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%